Omicron subvariant BA.5 is highly contagious but containable: Successful experience from Macau - Xu, Cong; Wang, Jue; Yu, Lili; Sui, Xinbing; Wu, Qibiao (Frontiers in Public Health, 2023)
The BA.5 variant of Omicron has been spreading rapidly throughout the world and leads to a significant rise in new cases and health concerns amid the ongoing wave of the COVID-19 pandemic. It has gradually become the dominant strain of the SARS-CoV-2 virus in many parts of the world and has been associated with the rapidly escalating COVID-19 cases and hospitalizations. A BA.5 infection surge burst out on 18 June 2022 and brought an unprecedented challenge to Macau, the most densely populated region worldwide, resulting in 1,821 new cases, which was significantly more than the cumulative cases of the previous variants of COVID-19 in Macau, suggesting that BA.5 is more transmissible than the previous subvariants. Fortunately, after 6-week concerted efforts, Macau effectively controlled the outbreak, with an infection rate of 0.27%, which was much lower than that in some BA.5-attacked regions, such as the US and Europe. Macau took a comprehensive anti-epidemic strategy to win a quick victory against BA.5, especially the ‘relatively static’ strategy that was first formulated and applied by Macau for the management of the COVID-19 pandemic. Successful experience showed that although BA.5 was highly contagious, it could be contained by comprehensive anti-epidemic measures, including adequate anti-epidemic preparation, herd immunity through vaccination, repeated mass nucleic acid tests and rapid antigen tests, KN-95 mask mandate, the ‘relatively static’ strategy, precise prevention and control, epidemiological investigation and tracing, and traditional Chinese medicine treatment, etc. Macau’s experience may offer hints for the regions experiencing the BA.5 waves to choose or adjust a more suitable anti-epidemic strategy. Keywords: Omicron subvariant BA.5, anti-epidemic strategy, contagious, experience, Macau